DETERMINANT FACTORS OF CUSTOMER SATISFACTION : EVIDENCE ON UNWIM FUTSAL SPORT - Amelia, Risna; Nurhidayati, Ninin; Hadiaty, Fifit (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
The purpose of this study was to find out how product quality, price, customer satisfaction and how much the influence is on customer satisfaction at Unwim Futsal Sport. In this study, there are three variables, those are product quality as the independent variable (X1), then price as the independent variable (X2) and customer satisfaction as the dependent variable (Y). The method used is descriptive analysis method to identify the problem of how product quality, price and how customer satisfaction are at Unwim Futsal Sport. Meanwhile the verificative analysis method is used to identify the problem of how much the influence of product quality and price have on customer satisfaction at Unwim Futsal Sport. The data collection technique uses primary data including interviews, observations and questionnaires that distributed to 100 respondents of Unwim Futsal Sport customers. As for the secondary data is obtained through literature study. To measure the effect of product quality and price on customer satisfaction, the researcher uses simple linear regression analysis and the coefficient of determination with the MSI and SPSS 20 programmes For Windows. Based on the results of the research, Product Quality has a significant effect on Customer Satisfaction. Price has a significant effect on Customer Satisfaction. Based on the results of simultaneous tests, Product Quality and Customer Satisfaction have a significant effect.